2010
DOI: 10.1093/ije/dyq162
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic X-rays and risk of childhood leukaemia

Abstract: The results suggest that exposure to post-natal diagnostic X-rays is associated with increased risk of childhood ALL, specifically B-cell ALL, but not AML or T-cell ALL. Given the imprecise measures of self-reported X-ray exposure, the results of this analysis should be interpreted with caution and warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 23 publications
5
81
1
1
Order By: Relevance
“…Some other researchers have also reported results similar to our study (Bartley et al, 2010;Hassanzadeh et al, 2011). This could be partly explained by younger age of marriage and pregnancy especially in rural areas and the effect of genetics and other environmental factors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Some other researchers have also reported results similar to our study (Bartley et al, 2010;Hassanzadeh et al, 2011). This could be partly explained by younger age of marriage and pregnancy especially in rural areas and the effect of genetics and other environmental factors.…”
Section: Discussionsupporting
confidence: 92%
“…This study has found an association of mothers having lower education with increased risk of leukemia in children. However, such association was not reported in earlier studies (Bartley et al, 2010;Hassanzadeh et al, 2011).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…These tests frequently included radiographs and CT scans, both of which have been associated with an increased risk of cancer when administered during infancy. [25][26][27][28][29][30][31][32] Parents accessing the blog shared their concern about these diagnostic procedures. Because DSFC is a benign condition, observation is the best plan, and multiple diagnostic tests are unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…résultats divergents, certaines montrant une augmentation du risque de cancer après exposition aux examens radiologiques dans l'enfance (Shu et al, 1994 ;Infante-Rivard et Jacques, 2000 ;Bartley et al, 2010), d'autres ne retrouvant pas d'excès de risque (Meinert et al, 1999 ;Shu et al, 2002 ;Rajamaran et al, 2011).…”
Section: Contexteunclassified